The implications of health education in Islamic education books (developed) for the basic intermediate stage in Jordan - Abu Ghalyoun, Eid Ismail (Journal of Educational and Psychological Sciences, 2018)
The study aimed identifying the extent to which Islamic education textbooks developed for the basic intermediate stage in Jordan included the contents of Health Education. The study tool was developed in a list representing the contents of contemporary professional education. It consisted of four fields; (22) enclosure. The content analysis method has been used where the wholesale and semi- sentence and unit of analysis have been taken, down to the quantitative data of the duplicates and percentages. The results revealed that books of Islamic education (developed) for the basic intermediate stage in Jordan did For grades (fourth,fifth,sixth) not take into consideration the contents of health education and the principle of sequence, and did not adopt a clear methodology, but rather a traditional, random curve in dealing with the contents of the study. The results showed that the field of mental health and its contents ranked first with a percentage of 46.7%, followed by the field of environmental health and its contents in the second place with a percentage of 37.1%, followed by the area of ​​personal health and its contents in third place and by 17.1% The last place is food health.The study recommended the following: - Reviewing the content of the books of Islamic education developed for the basic intermediate stage in Jordan including the contents of health education, and the extent to which they respect the principles of integration and sequence and the principles of self- learning and structural in addressing them.
Keywords: Developed Islamic Education Books; Health Education Contents; Intermediate Basic Stage.